2021
DOI: 10.3389/fpls.2021.742504
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Reveals the Positive Role of Abscisic Acid in Endodormancy Maintenance of Leaf Buds of Magnolia wufengensis

Abstract: Magnolia wufengensis (Magnoliaceae) is a deciduous landscape species, known for its ornamental value with uniquely shaped and coloured tepals. The species has been introduced to many cities in south China, but low temperatures limit the expansion of this species in cold regions. Bud dormancy is critical for plants to survive in cold environments during the winter. In this study, we performed transcriptomic analysis of leaf buds using RNA sequencing and compared their gene expression during endodormancy, endodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 86 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…Auxin influence many plant growth regulating functions during developmental processes, such as cell division, elongation, and differentiation ( Swarup et al, 2002 ; Yang et al, 2021 ; Xiong et al, 2022 ). Likewise, IBA is also known as a growth booster for the plant that regulates plant functions regards to roots, such as elongation, root hair development, lateral root formation, secondary metabolism, and nutrient transport ( Muday et al, 2012 ; Damodaran and Stra, 2019 ; Wu et al, 2021 ). Recently, Meng et al (2019) reported IBA treatment significantly enhanced the plant hormones at 3 days compared to control in apple rootstocks.…”
Section: Discussionmentioning
confidence: 99%
“…Auxin influence many plant growth regulating functions during developmental processes, such as cell division, elongation, and differentiation ( Swarup et al, 2002 ; Yang et al, 2021 ; Xiong et al, 2022 ). Likewise, IBA is also known as a growth booster for the plant that regulates plant functions regards to roots, such as elongation, root hair development, lateral root formation, secondary metabolism, and nutrient transport ( Muday et al, 2012 ; Damodaran and Stra, 2019 ; Wu et al, 2021 ). Recently, Meng et al (2019) reported IBA treatment significantly enhanced the plant hormones at 3 days compared to control in apple rootstocks.…”
Section: Discussionmentioning
confidence: 99%